2007
DOI: 10.1007/s12119-007-9012-8
|View full text |Cite
|
Sign up to set email alerts
|

Hip Hop Honey or Video Ho: African American Preadolescents’ Understanding of Female Sexual Scripts in Hip Hop Culture

Abstract: This qualitative study identifies African American preadolescents' acceptance and usage of Stephens and Phillips (2003) sexual scripts-the Diva, Gold Digger, Freak, Dyke, Gangster Bitch, Sister Savior, Earth Mother, and Baby Mama. These eight sexual scripts were found to be recognized and have shared meanings about sexual behaviors for participants. In turn, these were found to influence participants' conceptualizations of their own and general African American female sexuality, which differed significantly ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…In an earlier study of African American adolescents' responses to these sexual images, we (Stephens & Few, 2007) found that the descriptive titles and associated behaviors were universally identifiable and understood. This negotiation of these eight cultural images and interpersonal level messages relies on individuals' understanding of their own identity's relationship to the sexual images and the internalization messages (Stephens & Phillips, 2005).…”
Section: Eight Women: Sexual Images Of African American Women's Sexuamentioning
confidence: 85%
See 2 more Smart Citations
“…In an earlier study of African American adolescents' responses to these sexual images, we (Stephens & Few, 2007) found that the descriptive titles and associated behaviors were universally identifiable and understood. This negotiation of these eight cultural images and interpersonal level messages relies on individuals' understanding of their own identity's relationship to the sexual images and the internalization messages (Stephens & Phillips, 2005).…”
Section: Eight Women: Sexual Images Of African American Women's Sexuamentioning
confidence: 85%
“…African American adolescents' ideas about the self as a racial minority are developed through the understanding of symbols and meanings of their position within their family, community, or society. For example, prior research has shown that parents are the primary socialization forces for developing African American adolescents' positive attitudes toward physical attractiveness and cultural beliefs or norms (see Stephens & Phillips, 2003Stephens & Few, 2007). Peers are also important for shaping ideas about racial and cultural norms.…”
Section: Identity Development Among African American Early Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hale's definition reminds us that identity is a broad term referring to a wide variety of reference points which individuals attach themselves to. Thus, identity operates simultaneously across multiple axes of identification, including gender, nationality, class, race, and ethnicity (Alleyne 2002;Lopez 2003a;Lopez 2003b;Massey and Sánchez R. 2010;Rahier 1999b;Stephens and Few 2007;Stepick, Dutton Stepick, and Vanderkooy Forthcoming;Warikoo 2011). After establishing a theoretical context for the discussion, I then turn to a brief overview of several key areas within the identification literature.…”
Section: Literature On Identitymentioning
confidence: 99%
“…Thus, identifications occur within a specific historical, contextual, and temporal setting (Hintzen and Rahier 2003;Rahier, Hintzen, and Smith 2010;Stephens and Few 2007;Stephens and Phillips 2005;Stephens, Phillips, and Few 2009;Thomas and Clarke 2006). In order to better understand the emergence of current perspectives and theories of identification, an examination of past scholarship is in order.…”
Section: Identity or Identification?mentioning
confidence: 99%